Economic, practical impacts of precision farming – with especial regard to harvesting - Szolnoki , Ágnes; Nábrádi , András (Applied Studies in Agribusiness and Commerce, 2014)
Today agricultural practice is faced with a paradigm shift. In terms of natural resources, the World’s growing population calls for rational management and environment-conscious behaviour. Precision farming may provide a solution for the above mentioned criteria and problems. It has an array of technological equipment, elements and complete systems which are in themselves suitable to create conditions for efficient farming, to reduce environmental load and to provide farmers with optimal return on their investment. Agricultural production has started to focus mainly on efficient crop production and machine operation. Due to this trend, machinery exploitation emerges as a secondary priority for agricultural enterprises. The underlying reason behind this shift is primarily the rise of machinery operation costs. Efficient machinery operation can provide farmers with a solution to reduce their expenditure and through better logistical organization they can obtain extra returns. On the leading edge of my research is to introduce, quantitatively underpin and to justify the application of precision technologies. Our fundamental research methods rely on scenarios and economic calculations.